2018
DOI: 10.1155/2018/9415093
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Video Game Training with and without Subpatelar Bandage in Mobility and Gait Speed on Elderly Female Fallers

Abstract: Objectives The aim of the study was to investigate the effect of balance training with Nintendo Wii technology, with and without the use of additional sensory information (subpatellar bandage), in the functional mobility and gait speed of elderly female fallers. Methods Twenty elderly women were divided into two groups: group I: trained with the use of the Nintendo Wii; group II: trained using the Nintendo Wii and the addition of sensory information (subpatellar bandage). The functional mobility was assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Training with the use of VR affects the improvement of these functions; however, its effectiveness in this area has been proven only in patients with knee OA [ 24 ]. However, it has been noted that training on VR stability platforms has contributed to improving mobility and gait rate in women with risk of falls [ 54 ] as well as in the elderly people [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Training with the use of VR affects the improvement of these functions; however, its effectiveness in this area has been proven only in patients with knee OA [ 24 ]. However, it has been noted that training on VR stability platforms has contributed to improving mobility and gait rate in women with risk of falls [ 54 ] as well as in the elderly people [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Figure 7 , the 57 studies were mainly classified into three intended purpose settings: 49% applied VR and AR for training purposes, 46% for rehabilitation purposes, and only 5% for healthcare. For training purposes, the studies applied VR and AR to train and maintain different QoL domains, such as cognitive and physical functions in older adults 81 100 or psychological and social functions. 59 , 101 , 102 …”
Section: Resultsmentioning
confidence: 99%
“…As depicted in the bubble chart in Figure 9 , balance ( n = 24) was the common physical function among the reviewed studies, using motion-based exergame ( n = 15) 33 , 84 , 85 , 87 89 , 92 , 93 , 96 , 97 , 104 , 109 , 110 , 119 , 120 and immersive VR exergame ( n = 3). 100 , 108 , 121 For studies on gait ( n = 14) 88 , 89 , 92 , 93 , 96 , 97 , 100 , 104 , 109 , 114 , 115 , 119 121 and muscular strength ( n = 10), most of them utilized VR based game. 87 , 89 , 93 , 99 , 100 , 103 , 104 , 121 123 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carvalho et al showed an increase in gait speed and a decrease in the TUG time in elderly female fallers after 12 weeks of training (two sessions per week) with commercialized games of Wii Fit by Nintendo ® in sync with the Wii Balance Board ® [55]. Three different games were used for postural balance training: Penguin Slide, where the participants had to catch fish while balanced on a piece of ice by shifting their weight from side to side; Table Tilt, where participants move their bodies in various directions to put balls into holes; and Tightrope, where participants walk on a tightrope with several vertical jumps to avoid obstacles.…”
Section: Video Gamesmentioning
confidence: 99%